Adrenal pheochromocytoma as a rare cause of reversible left ventricular systolic dysfunction and malignant arrhythmias: a case series - Jenča, Dominik; Kubánek, Miloš; Kudla, Michal; Solar, Nevenka; Kautzner, Josef (European heart journal. Case reports, 2022)
Background: Pheochromocytoma is a neuroendocrine tumour originating from the chromaffin cells of adrenal glands or sympathetic paraganglia. It produces most frequently norepinephrine, epinephrine, and dopamine. As a result of non-specific and variable clinical presentation, pheochromocytoma is difficult to diagnose. Case summary: A 37-year-old female without medical history and 57-year-old male patient with diabetes, arterial hypertension, and aortic valve replacement with a mechanical prosthesis were admitted to the hospital after successful cardiopulmonary resuscitation due to ventricular fibrillation. In both patients, coronary angiography demonstrated a normal finding, and echocardiography showed left ventricular (LV) contractile dysfunction with improvement in the subsequent examination. In the first patient, the diagnosis of stress-induced cardiomyopathy was considered as the most probable cause. She was later admitted to hospital due to acute pulmonary oedema with hypertensive crisis. Echocardiography documented reversible LV systolic dysfunction with improvement after 3 days. The course of hospitalization of the male was complicated by multi-organ dysfunction syndrome comprising renal failure, paralytic ileus, and pancreatic irritation, which normalized after 2 weeks. The diagnosis of pheochromocytoma was confirmed by laboratory tests and imaging methods. After pharmacological pre-treatment with doxazosin in both patients and bisoprolol in the female, successful adrenalectomies were performed with no relapse of tumour. Discussion: We describe an atypical clinical presentation of pheochromocytoma with initial cardiac arrest due to ventricular fibrillation and reversible LV systolic dysfunction. Our cases underline that clinical suspicion of pheochromocytoma as a potentially correctable cause should be raised in unexplained cases of severe heart failure, ventricular arrhythmias, and cardiac arrest.